2011
DOI: 10.1510/icvts.2011.271932
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral simultaneous inflammatory myofibroblastic tumor of the lung with distant metastatic spread

Abstract: Inflammatory myofibroblastic tumors (IMT) of the lung are considered rare and benign; however, involvement of adjacent thoracic organs, local recurrence and distant metastases have been described. The potential presence of distant metastases supports the hypothesis that those tumors should not be considered 'clinically' benign, although histological features suggest this attitude; thus, complete resection and careful follow-up are mandatory. We present a case of a bilateral pulmonary IMT with left adrenal glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…Presently, it is believed to be a low-grade benign tumor characterized by the presence of a clonal population of cells; however, it has been known to occasionally behave in a locally invasive manner and even to metastasize. 4 The histopathologic appearance is characterized by the presence of myofibroblastic spindle-shaped cells in the background of an inflammatory cell infiltrate consisting of lymphocytes, plasma cells, and eosinophils. The cells are nonreactive for IgG4, which excludes IgG4-related pseudotumor, a close differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, it is believed to be a low-grade benign tumor characterized by the presence of a clonal population of cells; however, it has been known to occasionally behave in a locally invasive manner and even to metastasize. 4 The histopathologic appearance is characterized by the presence of myofibroblastic spindle-shaped cells in the background of an inflammatory cell infiltrate consisting of lymphocytes, plasma cells, and eosinophils. The cells are nonreactive for IgG4, which excludes IgG4-related pseudotumor, a close differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…IMT may occur at any age, but usually affects children and adults <40 years old (6,11). IMT primarily affects the lung, and accounts for 0.04–1% of all reported lung tumors (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Carillo et al 5 and Gallego et al 9 have reported cases of IMT of the lung with adrenal gland and maxillary metastases, respectively. The term, IFS has been utilised to classify these tumours with aggressive nature and metastases 3 9…”
Section: Discussionmentioning
confidence: 99%
“…However, the term IMT was coined around two decades ago owing to its distinctive pathological and molecular features 7. Although these tumours were initially regarded to be benign and non-neoplastic, it is now widely accepted that these tumours may have a tendency to grow aggressively leading to local invasion to adjacent organs, recurrence and distant metastasis 5 9…”
Section: Introductionmentioning
confidence: 99%